The Effectiveness of Cognitive Behavioral Therapy Techniques on Academic Anxiety in Final Year Students - Salsabilla, Najwa Inaya; Wahyunengsih; Sari, Adelia Puspita (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2022)
This study aimed to determine the effectiveness of Cognitive Behavioral Therapy (CBT) techniques on academic anxiety problems that occur in final year students. The object of this research is final year students who have academic anxiety problems. The method used in this study is a qualitative descriptive method with a case study approach, where the researcher deepens the problem with the subject through various information about the factors that cause academic anxiety and then after therapy how the changes, so that it will be able to describe how the CBT technique can be implemented. Data collection is done by interviewing counselors. The results showed that the Cognitive Behavior Therapy technique could reduce final-year students’ academic anxiety.